The proto-oncogene Myc drives expression of the NK cell-activating NKp30 ligand B7-H6 in tumor cells. (2nd July 2016) - Textor, Sonja; Bossler, Felicitas; Henrich, Kai-Oliver; Gartlgruber, Moritz; Pollmann, Julia; Fiegler, Nathalie; Arnold, Annette; Westermann, Frank; Waldburger, Nina; Breuhahn, Kai; Golfier, Sven; Witzens-Harig, Mathias; et al.
ABSTRACT: Natural Killer (NK) cells are innate effector cells that are able to recognize and eliminate tumor cells through engagement of their surface receptors. NKp30 is a potent activating NK cell receptor that elicits efficient NK cell-mediated target cell killing. Recently, B7-H6 was identified as tumor cell surface expressed ligand for NKp30. Enhanced B7-H6 mRNA levels are frequently detected in tumor compared to healthy tissues. To gain insight in the regulation of expression of B7-H6 in tumors, we investigated transcriptional mechanisms driving B7-H6 expression by promoter analyses. Using luciferase reporter assays and chromatin immunoprecipitation we mapped a functional binding site for Myc, a proto-oncogene overexpressed in certain tumors, in the B7-H6 promoter. Pharmacological inhibition or siRNA/shRNA-mediated knock-down of c-Myc or N-Myc significantly decreased B7-H6 expression on a variety of tumor cells including melanoma, pancreatic carcinoma and neuroblastoma cell lines. In tumor cell lines from different origin and primary tumor tissues of hepatocellular carcinoma (HCC), lymphoma and neuroblastoma, mRNA levels of c-Myc positively correlated with B7-H6 expression. Most importantly, upon inhibition or knock-down of c-Myc in tumor cells impaired NKp30-mediated degranulation of NK cells was observed. Thus, our data imply that Myc driven tumors could be targets for cancer immunotherapy exploiting the NKp30/B7-H6 axis.